Polyphenols and Organic Acids as Alternatives to Antimicrobials in Poultry Rearing: A Review - Federica Scicutella; Federica Mannelli; Matteo Daghio; Carlo Viti; Arianna Buccioni (MDPI AG, 2021)
For decades antibiotics have been used in poultry rearing to support high levels of production. Nevertheless, several problems have arisen because of the misuse of antibiotics (i.e., antibiotic resistance, residues in animal products, environmental pollution). Thus, the European Union (EU) as well as the European Food Safety Authority (EFSA) promote action plans to diminish the use of antibiotics in animal production. Alternatives to antibiotics have been studied. Polyphenols (PPs) or organic acids (OAs) seem to be two accredited solutions. Phenolic compounds, such as phenols, flavonoids, and tannins exert their antimicrobial effect with specific mechanisms. In contrast, short chain fatty acids (SCFAs) and medium chain fatty acids (MCFAs), the OAs mainly used as antibiotics alternative, act on the pathogens depending on the pKa value. This review aims to collect the literature reporting the effects of these substances applied as antimicrobial molecules or growth promoter in poultry feeding (both for broilers and laying hens). Organic acids and PPs can be used individually or in blends, exploiting the properties of each component. Collected data highlighted that further research needs to focus on OAs in laying hens' feeding and also determine the right combination in blends with PPs.